CT of the Peritoneum - Rossi, Armando (Medical Radiology, Diagnostic Imaging., 2001)
This superbly illustrated book, by two of the leading radiologists in Italy, is the first to be devoted entirely to computed tomography of the peritoneum. The case documentation encompasses both common and rare pathological conditions, and is the product of 20 years of painstaking research. The first part of the book is devoted to normal anatomy, physiology and physiopathology, CT techniques, and CT anatomy. The second part comprises nine chapters that systematically discuss and illustrate primary and secondary pathology of the peritoneum. The topics covered include fluid collections and effusions, acute and chronic inflammatory processes, post-traumatic lesions, hernias, cysts, primary tumors, and metastases. This book will be invaluable in improving knowledge of a topic that cannot be treated in detail in general texts on abdominal CT. Furthermore, it will be of great assistance to both radiologists and clinicians in resolving difficult and urgent diagnostic problems encountered during their everyday work.